The vicariate forane and its offices - ADAMCZYK, JERZY (Prawo Kanoniczne, 2018)
The aim of this article is to discuss the institution of the vicariate forane and its offices in the canonical aspect. The first part focuses on the issues of nomenclature, definition and the establishment of the vicariate forane. The second part emphasizes the tasks of the vicariate forane, while the third one is devoted to particular positions in the institution of the vicariate forane.